Seeking Slang Words in "Last One Standing" Song: A Sociolinguistic Analysis - Rahardi, Panggih (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2023)
Sociolinguistics is the general term for the study of language that pays attention on the social aspects of language. This study focused on the role of language in society, or how members of various groups utilize language to communicate with one another. One of the many variations in language usage is slang. Therefore, the objectives of this study were to identify the types of slang and find the most frequent type of slang word in the "Last One Standing" song written by Skylar Grey. This study employed a qualitative descriptive approach since the researcher described the word development process of slang words in the song in detail. Documentation method was used to collect data for this study, which subsequently employed Yule's (2010) word formation processes to examine the slang words. Only six of eleven kinds were identified by the researcher: etymology, coinage, compounding, blending, clipping, and acronym. Based on the data, clipping is the most frequent slang in this song. It is hoped that this study would aid future sociolinguistics research, particularly slang analysis.